2022
DOI: 10.2196/41697
|View full text |Cite
|
Sign up to set email alerts
|

A Video-Delivered Family Therapeutic Intervention for Perinatal Women With Clinically Significant Depressive Symptoms and Family Conflict: Indicators of Feasibility and Acceptability

Abstract: Background Variation in family therapeutic intervention fidelity has an impact on outcomes. The use of video conferencing technology can strengthen therapist fidelity to family therapeutic interventions. Objective This article explores indicators of feasibility and acceptability for a video-delivered family therapeutic intervention for perinatal women with depressive symptoms and family conflict. The objectives of this article are to describe indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The results of the preliminary pilot study of REST with home-visited families showed that it significantly reduced maternal depressive symptoms and family conflict [24]. Although the participants in this study had an overall higher level of education and greater financial security than those who participated in other studies of REST [24][25][26], the severity levels for maternal depressive symptoms and family conflict are similar. This study expands the existing research on REST to explore its impact on perinatal anxiety.…”
Section: Framework Of Fbccmmentioning
confidence: 57%
See 3 more Smart Citations
“…The results of the preliminary pilot study of REST with home-visited families showed that it significantly reduced maternal depressive symptoms and family conflict [24]. Although the participants in this study had an overall higher level of education and greater financial security than those who participated in other studies of REST [24][25][26], the severity levels for maternal depressive symptoms and family conflict are similar. This study expands the existing research on REST to explore its impact on perinatal anxiety.…”
Section: Framework Of Fbccmmentioning
confidence: 57%
“…A preliminary pilot study of REST showed that it was feasible and acceptable for socioeconomically disadvantaged families [24]. A pilot randomized trial is currently underway that is testing REST's impacts on depression and family function in a more diverse population of families [26], and the results will be published in a subsequent journal paper.…”
Section: Principal Resultsmentioning
confidence: 99%
See 2 more Smart Citations